Expression of acute phase proteins and inflammatory cytokines in mouse mammary gland following Staphylococcus aureus challenge and in response to milk accumulation. Issue 4 (November 2014) - Nazemi, Sasan; Aalbæk, Bent; Kjelgaard-Hansen, Mads; Safayi, Sina; Klærke, Dan Arne; Knight, Christopher H
<x content-type="archive" xml:space="preserve">Abstract</x> We used a mouse model of pathogenic (Staphylococcus aureus) and non-pathogenic (teat sealing) mammary inflammation to investigate mRNA expression of several inflammatory cytokines and acute phase proteins (APP) in mammary tissue and liver, and the appearance of some of these factors in plasma and milk. The expression levels of IL1β and TNFα were markedly up-regulated in Staph. aureus-inoculated mammary tissue at 72 h, whilst IL6 was up-regulated to a lesser extent in a way which was not confined to the inoculated glands. APP expression was up-regulated at 48 and 72 h in both Staph. aureus-inoculated and teat-sealed mammary glands. These differences between cytokine and APP expression provide additional support for the contention that APPs are produced within the mammary tissue itself during inflammation, rather than in associated immune cells. We propose that measurement of cytokines and APP in combination might provide a tool for diagnostic discrimination between mastitis caused by pathogenic invasion and milk accumulation, and hence allow for better targeting of antibiotic therapy. In comparison with mammary expression, expression of cytokines in liver tissue was up-regulated to a similar or lesser extent, whilst expression of APP was up-regulated to a much greater extent. The first appearance of increased cytokine and APP concentrations in plasma and of milk amyloid A (MAA) in milk occurred in advance of the measurable up-regulation of expression, hence their origin cannot be stated with certainty.